USING THE SAO IMAGE DS9 PROGRAM IN FORMING SCIENTIFIC ANALYTICAL COMPETENCE IN FUTURE PHYSICS AND ASTRONOMY TEACHERS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the experience of using the modern astronomical data visualization and analysis program - SAOImage DS9 - in the process of forming scientific analysis competence in future physics and astronomy teachers. The possibilities of strengthening theoretical knowledge and developing practical scientific analysis skills through the study of real astronomical observation data using the DS9 program are shown. As an example, as part of an independent research project, gravitationally lensed quasar images obtained in the optical range with the AZT-22 telescope of the Maidanak Observatory were analyzed in the DS9 program. The article presents and discusses the methodology of this project, the results obtained - in particular, the photometry of quasar images, light curves and analysis of the lensing effect. The results show that such a practical assignment using the DS9 program is effective in forming scientific analysis competence in teacher training, and increases students' skills in the practical application of theoretical knowledge, working with digital data and drawing scientific conclusions.